Starting Online Services at University Clinics at the Beginning of the Covid-19 Pandemic - Dhanasari Vidiawati Trisna; Riri Indriyanti; Mora Claramita (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
The UI Makara Satellite Clinic (KSUI) is a university clinic that serves UI residents and the public as well as a vehicle for  education  and  health  research  in  primary  services.  It has been  a  BPJS  Outpatient  Service  Clinic  (KPRJ)  since October  2018.  It  is  called  a Satellite  Clinic  because  it  is planned  to  become  a  satellite  for  university  hospitals  in the academic health system at the University of Indonesia. Currently, KSUI is located on the Depok campus and the Salemba campus. In its daily services at the Depok campus, KSUI provides  services  for  doctors,  dentists,  nursing, pharmacy,  laboratories,  action  rooms, and psychological counseling.KSUI’s mission is not the same as an ordinary outpatient clinic, but because KSUI is a health service facilitated by the university, KSUI has a mission to maintain the health of the academic community, and not only treat them when they fall  ill.  Therefore,  in  addition  to  services that  respond  to patients coming to the clinic, KSUI also organizes periodic health check services, facilitates Posbindu activities in the faculties and office buildings on campus, and participates in medical care at any gathering or sports activities provided on campus.With  the  Covid-19  case  being  found  in  Indonesia,  KSUI decided  to  change  its service  method  as  quickly  and  as firmly  as  possible  from  face-to-face  services  to online services,  following  the  Chancellor’s  Decree  to  close  the campus  from  face-to-face  learning  and  other  student activities.  With  the  return  of  the  UI  dormitory students and  the  implementation  of  work  from  home  (WFH)  for lecturers  and education  staff,  KSUI  must  provide  safe services during a pandemic and can be accessed by service users  without  having  to  come  to  campus.  Therefore,  this article is a brief piece of information that has been done by KSUI when it decided that services should be carried out online.  It  is  not  easy  for  the  officer,  because  it  has  never been done, and it is not easy for the patient.